A Comparative study of the student teaching program in some selected primary teacher training institutions in the Philippines - Toprasirt, Amnuay 1935- (s.n.], 1966)
This study compared the student teaching programs of three primary teacher training institutions in the Philippines. The institutions selected are the Philippine Normal College, the Zamboanga Normal College and the Cebu Normal School. The study partially determined the organization and administration of student teaching, the supervision, the evaluation, and the problems encountered in student teaching by persons involved in the program. Through this study, contributions to the improvement of the practices of student teaching in Thailand can be made.